Teorie poetów. Manifesty późnoawangardowe i poetyckie programy - Orska, Joanna (Przestrzenie Teorii, 2021)
This research paper considers the avant-garde manifestos and programmatic statements of poets,in the light of the debate on the emancipatory potential of neoavant-garde art. The author shows the need to redefine the notion of artistic autonomy that new art programmes involve. In the first part of the article, the point of origin of the modern understanding of artistic autonomy is reflected on in its two basic formulas: Kantian and Hegelian. The second part evolves an analysis of three examples of contemporary metapoetic statements by Polish poets (Piotr Sommer, Andrzej Sosnowski, Kacper Bartczak). Their neoavant-garde premises of the performative character of the theoretical discussions, and of the artistic elements that connect their theoretical ideas to the actual works of these poets lead us to the conclusion that engaged, activistic poetic practice, concerning he rules directed by the questions of autonomy of art, cannot be judged from the point of view of the Kantian definition of this autonomy, especially if we take the poetical matter of avant-garde provenance into consideration.